Pharmacogenetic allele nomenclature: International workgroup recommendations for test result reporting. Issue 2 (20th November 2015) - Kalman, LV; Agúndez, JAG; Appell, M Lindqvist; Black, JL; Bell, GC; Boukouvala, S; Bruckner, C; Bruford, E; Caudle, K; Coulthard, SA; Daly, AK; Tredici, AL Del; et al.
Abstract : This article provides nomenclature recommendations developed by an international workgroup to increase transparency and standardization of pharmacogenetic (PGx) result reporting. Presently, sequence variants identified by PGx tests are described using different nomenclature systems. In addition, PGx analysis may detect different sets of variants for each gene, which can affect interpretation of results. This practice has caused confusion and may thereby impede the adoption of clinical PGx testing. Standardization is critical to move PGx forward.